Analysis of artificial intelligence chatbots and satisfaction for learning in mathematics education - Moral-Sánchez, Silvia Natividad; Ruiz-Rey, Francisco José; Cebrián-de-la-Serna, Manuel (Universidad Pablo de Olavide, 2023)
The use of artificial intelligence (AI) is becoming increasingly widespread in today’s society. This type of technology, and more specifically chatbots as virtual assistants, can be implemented and integrated as a support tool in educational environments. This article proposes the creation of chatbots in the subject of didactic of geometry of the Degree of Primary Education of the Faculty of Education at the University of Málaga, carried out by 120 students in two groups. The aim is to analyse these chatbots, as well as the students’ evaluation and satisfaction with them. To this end, the students were given brief training so that they could generate their own bots and know how to integrate them into a social network and then use them. The results of the questionnaire show that the students have shown interest in the generation of their chatbot and its integration into the social network, have improved their digital competence, as well as demonstrating a high degree of satisfaction with their AI creations, along with the idea that this type of experience can be transferred to other subjects and educational contexts.
Análisis de chatbots de inteligencia artificial y satisfacción en el aprendizaje en educación matemática
Keywords: Investigación activa en educación; Matemáticas - Estudio y enseñanza; Inteligencia artificial en la enseñanza; Chatbots; Mathematics education; Artificial intelligence; Teaching and learning